Research on clinical, biological characteristics, and treatment of hyperkalemia in acute kidney injury patients - Tran, Thuy Quynh; Vo, Tam; Hoang, Trong Hanh; Dam, Trung Nghia; Hoang, Anh Tien (Tạp chí Y Dược Huế, 2026)
Purpose: This study investigated the clinical and paraclinical characteristics and severity of hyperkalemia in patients with acute kidney injury (AKI) treated in the Intensive Care Unit of Hue Central Hospital, and evaluated treatment outcomes and associated factors. Methods: A total of 121 AKI patients treated from March 2022 to June 2023 were included. Data on medical history, clinical features, laboratory findings, and hyperkalemia treatment outcomes were collected and analyzed. Results: Hypertension was the most common comorbidity (38.8%), followed by pulmonary disease (34.7%) and diabetes (20.7%). AKI was most often detected during hospitalization (62.8%). The leading cause was sepsis/infection (90.9%), followed by nephrotoxic drugs (38.0%). Common clinical manifestations included dyspnea or tachypnea (86.0%), shock or cardiac arrest (76.0%), edema (60.3%), and fatigue (57.0%). Most patients had normal consciousness (66.9%), while 13.2% were comatose. Stage 3 AKI predominated (54.5%), with 60.3% having urine output < 0.5 ml/kg/hour. Electrocardiographic abnormalities included tachycardia or bradycardia (79.3%), ST segment depression (23.1%), flattened P waves (14.9%), and peaked T waves (13.2%). Hyperkalemia (serum potassium ≥ 5.5 mmol/L) occurred in 52.1% of patients, with severe hyperkalemia (≥ 6.5 mmol/L) in 10.7%. Mild hyperkalemia was most common (76.0%), while severe cases accounted for 21.5%. Calcium chloride was the most frequently used treatment (79.4%), followed by diuretics (63.5%), sodium bicarbonate (58.7%), and insulin with glucose infusion (57.1%). Continuous renal replacement therapy (CRRT) was applied in 19.0% of patients. Potassium levels normalized to < 5.5 mmol/L in 81.0% of patients within 6 hours and 84.1% after 6 hours. Serum potassium levels improved significantly after medical therapy or CRRT (P < 0.001). No significant associations were found between treatment outcomes and age, sex, BMI, admission characteristics, timing of detection, or hematological parameters. Conclusions: AKI patients in the ICU commonly presented with dyspnea and shock/cardiac arrest. Hyperkalemia was frequent (52.1%), including 10.7% severe cases, but potassium levels improved significantly with appropriate treatment.